Controversies on Psychoanalytic Psychotherapies: Is Psychodynamic Psychotherapy Effective for the Treatment of PTSD? - Becker, Joana Proença (2022)
Psychoanalysis is indispensable when writing and discussing traumatic stress, but in the treatment of these conditions it is ultimately disregarded. Since they are considered long-term treatments, therapies derived from psychoanalysis, such as Psychodynamic Psychotherapy (PDT), are not the first choice in health centers and clinics, which may be also a reflection of a scarcity of publications on its effectiveness. Through a literature review, focused on the effect size of PDT in the treatment of Posttraumatic Stress Disorder (PTSD), we have confirmed this scarcity. However, in the few studies conducted on this topic, findings have shown similarities between PDT and other therapies in reducing PTSD symptoms, both in post-therapy and follow-up assessments. The time of psychoanalytic psychotherapies is often pointed out as an obstacle, although studies have indicated that patients treated through these techniques present a continuous state of improvement.